EKSISTENSI KAIN IDUP PANAK SEBAGAI MEDIA KOMUNIKASI SOSIAL DI DESA TENGANAN KARANGASEM BALI - I Gusti Ngurah Agung Panji Tresna; Ida Bagus Sastra Lingga Kusuma (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
Idup Panak woven textil is one of the traditional textil in the Tenganan Pegringsingan Traditional Village. Idup Panak textil as a work of weaving art has its own uniqueness compared to other gringsing fabrics because it is made using leftover threads from other ready-made motifs. Idup Panak textil are starting to increase in existence and the quantity of sales is getting bigger. Of course, it is necessary to strengthen the principles of meaning and value in maintaining the quality of the textile, of course, in order to avoid a decline in cultural understanding. Departing from the problems above, this study aims to strengthen the construction of values ​​and principles contained in the Idup Panak textile. The method used is a qualitative research method using interview techniques, observation and literature in data collection. This study uses symbol theory which will assist in analyzing the symbols contained in the Idup Panak Textil and the Communication Strategy Theory which functions in the development of the Idup Panak Textil so that all forms of principle values ​​contained in the Idup Panak Textil are preserved. The results show that action has begun. duplication of Idup Panak Textil in order to meet consumer demand, this has resulted in craftsmen starting to experience social blindness which only prioritizes quantity and puts aside the meaning of value, it is very necessary to educate and supervise to face increasingly advanced developments bringing this tradition in a positive direction with meaning values ​​that are still maintained .